Kinetic modeling and simulation of methanogenic production in a batch reactor (Research, Society and Development, 2025)
Biochemical Methane Potential (BMP) assays are employed to assess the methane production potential of specific substrates, as they monitor the volume of biogas generated from organic waste, thereby evaluating its biodegradability through the total methane (CH₄) yield. Reactor modeling, in turn, enables the simulation of processes by predicting substrate consumption, microbial growth, and product formation. The main objective of this study was to predict the reaction behavior over time based on the concentration profile of a heterogeneous reaction, as well as to validate the model through comparison with experimental data. The results indicated that the reaction follows first-order kinetics, with a coefficient of determination close to 1, highlighting the accuracy of the mathematical model. The simulations successfully reproduced experimental behavior, validated the rate constant, and allowed extrapolations under different conditions, enabling practical applications. It was concluded that modeling is an effective tool for predicting system behavior under varying conditions, contributing to the advancement of technologies aimed at sustainable energy generation.